Effect of B doping on electrical and thermal properties of SiC bodies fabricated by spark plasma sintering. (2019) - Taki, Yukina; Kitiwan, Mettaya; Katsui, Hirokazu; Goto, Takashi
Abstract: B-doped SiC bodies were fabricated by spark plasma sintering at 2373 K, 50 MPa, 300 s in a vacuum and N2 atmosphere. The relative density of 1 mol% B doped-SiC body sintered in a vacuum and 5 mol% B doped-SiC body sintered in N2 atmosphere were 97 and 98%, respectively. The electrical conductivity of B-doped SiC bodies sintered in a vacuum with 0.5 mol% B and that with 1 mol% B sintered in N2 atmosphere showed semi-insulative conduction in the range of 3–5×10 -3 S m -1 at room temperature. The thermal conductivity of B-doped SiC body at 0.5 at% B sintered in a vacuum were 185 W m -1 K -1 while that at 1 at% B sintered in N2 atmosphere were 177 W m -1 K -1 at room temperature.